2017
DOI: 10.1155/2017/6250635
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Monolateral External Fixation and Internal Fixation for Skeletal Stabilisation in the Management of Small Tibial Bone Defects following Successful Treatment of Chronic Osteomyelitis

Abstract: Background To compare the salvage rate and complication between internal fixation and external fixation in patients with small bone defects caused by chronic infectious osteomyelitis debridement. Methods 125 patients with chronic infectious osteomyelitis of tibia fracture who underwent multiple irrigation, debridement procedure, and local/systemic antibiotics were enrolled. Bone defects, which were less than 4 cm, were treated with bone grafting using either internal fixation or monolateral external fixation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…When the infected site is close to the joint, transarticular fixation leads to joint stiffness [15], which is not conducive to the recovery of joint function. External fixation is bulky, which affects patients' ordinary life [16]. Long-term placement of the external fixation also has a negative impact on patients' mental health [17].…”
Section: Discussionmentioning
confidence: 99%
“…When the infected site is close to the joint, transarticular fixation leads to joint stiffness [15], which is not conducive to the recovery of joint function. External fixation is bulky, which affects patients' ordinary life [16]. Long-term placement of the external fixation also has a negative impact on patients' mental health [17].…”
Section: Discussionmentioning
confidence: 99%
“…[3] Debr. delayed CBG [26,36,44] Three stage [1] Debr. delayed CBG, delayed STC [33] Cancellous graft with AB [9] Two stage [6] Debr.…”
Section: Induced Membrane Techniquementioning
confidence: 99%
“…The study of Wang et al showed that there was no significant difference between the two methods for bone defects smaller than 4 cm, but external fixation showed a strong advantage instability when it was larger than 4 cm. 18 Currently, the more popular fixation technology is Ilizarov, which is not suitable for doctors in most grass-roots hospitals due to its long learning curve, long course of treatment, increased surgical trauma, and risk. Therefore, more studies may focus on simple and effective external fixation techniques in the treatment of bone defects in the future.…”
Section: Com Module Co-occurrence Results Analysismentioning
confidence: 99%